2012
DOI: 10.1021/jp306308w
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Monodispersed Silver Nanodecahedra with Optimal SERS Activities Using Seedless Photo-Assisted Citrate Reduction Method

Abstract: This article presents a mechanistic study of silver nanodecahedra prepared by the method of photoassisted sodium citrate reduction under irradiation of blue light-emitting diodes (LEDs). This synthesis of silver nanodecahedra can be easily reproduced in the absence of silver seeds and can be completed in one-pot. The data suggest a combination of two processes including gradual growth from multiple-twinned particles and subsequent plasmonmediated crystal growth. More than 85% of as-prepared silver nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 67 publications
(116 reference statements)
4
75
1
Order By: Relevance
“…[35,37,52,53,54] Additionally, nanodecahedra seeds synthesized in this manner can be further enlarged by the application of green (or other) light via LEDs to tune the Local Surface Plasmon Resonance (LSPR). [54] However, to the best of our knowledge, no results have been reported yet to synthesize high-yield silver nanodecahedra using green LEDs (or other green light sources) directly.…”
Section: Introductionmentioning
confidence: 99%
“…[35,37,52,53,54] Additionally, nanodecahedra seeds synthesized in this manner can be further enlarged by the application of green (or other) light via LEDs to tune the Local Surface Plasmon Resonance (LSPR). [54] However, to the best of our knowledge, no results have been reported yet to synthesize high-yield silver nanodecahedra using green LEDs (or other green light sources) directly.…”
Section: Introductionmentioning
confidence: 99%
“…20 32 33 Silver nanoparticles were chosen as SERS nanosubstrates to provide strongly enhanced spectroscopic signals owing to the localized electromagnetic filed present at metal surfaces. 34 Our previous study demonstrated that the shapes of silver nanoparticles have a great effect on SERS enhancement. 35 36 Therefore, it is interesting to compare the surface enhancement difference between the as-prepared silver nanoprisms and the silver nanodecahedra at different excitation wavelengths.…”
Section: Preparation Of Silver Nanoprisms Andmentioning
confidence: 98%
“…In general, all metals M for which E° < 1.00 V vs. SHE can be used as the sacrificial template to synthesize various shapes of AuM bimetallic NCs (the method has been optimized for various systems by Xia's group over the last decade [94,[140][141][142][143][144][145][146]). AgNCs are routinely synthesized via a one-pot synthesis such as polyol before a galvanic replacement reaction between the as-prepared sacrificial template and an aqueous HAuCl4 solution leading to hollow, porous AuNCs and Au nanocages [139,147]. A typical synthesis of Au nanocages involves 2.5 mL of the aqueous solution of HAuCl4 (175 μM) to be added to 5 mL AgNCs solution using a syringe pump at a rate of 250 μL•min −1 under magnetic stirring …”
Section: Noble Metal-based Electrodesmentioning
confidence: 99%
“…AgNCs are routinely synthesized via a one-pot synthesis such as polyol before a galvanic replacement reaction between the as-prepared sacrificial template and an aqueous HAuCl 4 solution leading to hollow, porous AuNCs and Au nanocages [139,147]. A typical synthesis of Au nanocages involves 2.5 mL of the aqueous solution of HAuCl 4 (175 µM) to be added to 5 mL AgNCs solution using a syringe pump at a rate of 250 µL·min −1 under magnetic stirring and the final product is centrifuged and then dispersed in water for utilization.…”
Section: Noble Metal-based Electrodesmentioning
confidence: 99%